2017
DOI: 10.3389/fphys.2017.00638
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a 100-km Ultra-Marathon under Freezing Conditions on Selected Immunological and Hematological Parameters

Abstract: Although moderate exercise is beneficial for the human body and its immune system, exhaustive ultra-endurance performance in cold conditions might be harmful. The aim of this study was to examine the effect of a 100-km ultra-marathon under cold conditions (temperatures from −1°C to +1°C) on selected immunological, biochemical and hematological parameters. Participants were 15 runners (12 men and three women, age 40.3 ± 9.7 years, body mass 67.3 ± 9.0 kg and body height 1.74 ± 0.10 m, mean ± standard deviation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 46 publications
1
32
0
2
Order By: Relevance
“…During intense physical exercise, an athlete's physiological status is expected to be associated with his or her immune response [5,6] since it produces a stress condition that triggers metabolic, endocrinological, neuropsychological, and immunological changes [4]. Accordingly, in the present study some cytokines were correlated with cortisol levels.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…During intense physical exercise, an athlete's physiological status is expected to be associated with his or her immune response [5,6] since it produces a stress condition that triggers metabolic, endocrinological, neuropsychological, and immunological changes [4]. Accordingly, in the present study some cytokines were correlated with cortisol levels.…”
Section: Discussionmentioning
confidence: 72%
“…Activities that involve intense, long-term physical exercise, such as orienteering, are known to be stressors and sources of physio-pathological changes [4]. The mechanisms of adaptation to stress and physical exercise have common elements, involving muscle injury and immune response activation.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that leucocyte counts and that of its subtypes increased more than 200% following continuous exercise for 30 min at all intensities, suggesting that there is a lower risk of heart attack when sedentary subjects in our study exercised for less than 30 min at a moderate intensity. Similarly, a significant increase in leucocytes was also found among endurance and sprint athletes [22][23][24][25][26]. A previous study also reported that the number of leucocytes is increased even 3 h after exercise [7].…”
Section: Discussionmentioning
confidence: 77%
“…The stress-related inflammation affects the bone marrow and leads to an increased leukocyte turnover (Spiropoulos et al, 2010 ). Markers of an inflammatory process include leucocytes (Jee et al, 2013 ; Bird et al, 2014 ; Chiu et al, 2015 ; Jastrzebski et al, 2016 ; Zakovska et al, 2017 ), C-reactive protein (Kim et al, 2009 ; Waśkiewicz et al, 2012 ; Kasprowicz et al, 2013 ), ferritin (Chiu et al, 2015 ), TNF-α (Nieman et al, 2000 ; Simons and Kennedy, 2004 ; Jee and Jin, 2012 ; Chiu et al, 2013 , 2015 ), blood sedimentation reaction, iron (Fallon, 2001 ), y-interferon (Simons and Kennedy, 2004 ), Interleukin 1 receptor antagonist (Nieman et al, 2000 ), Interleukin-1b (Simons and Kennedy, 2004 ; Gill et al, 2015b ), Interleukin-8 (Nieman et al, 2000 ; Gill et al, 2015b ), Interleukin-10 (Nieman et al, 2000 ; Simons and Kennedy, 2004 ; Gill et al, 2015b ) and Interleukin-6 (Fallon et al, 1999a ; Waśkiewicz et al, 2012 ; Kasprowicz et al, 2013 ).…”
Section: Immune Systemmentioning
confidence: 99%